Leading in the Digital World - Mukherjee, Amit (HighBridge, 2020)
Certain ideas about business leadership are held to be timeless, and certain characteristics of leaders-often including a square jaw, a deep voice, and extroversion-are said to be universal. In Leading in the Digital World, Amit Mukherjee argues that since digital technologies are changing everything else, how could they not change leadership ideologies and styles? As more people worldwide participate equally in business, those assumptions of a leader's ideal profile have become irrelevant. Drawing on a global survey of 700 mid-tier to senior executives and interviews with C-level executives from around the world, Mukherjee explains how digital technologies are already reshaping organizations and work and what this means for leaders. For example, globally dispersed businesses can't reserve key leadership roles for people from exclusive groups; leadership must become inclusive, or fail. Leaders must learn to collaborate in a multipolar world of networked organizations, working with co-located and non-co-located colleagues. Leaders must lead for creativity rather than productivity. Focusing on practice, Mukherjee outlines goals and strategies, warns against unthinking assumptions, and explains how leaders can identify the mindsets, behaviors, and actions they need to pursue.
Online resource; Title from title page (viewed June 30, 2020)
Keywords: Audiobooks; Livres audio; Downloadable audio books